Mengolah Bawang Merah dan Cara Membuat Kartu Keluarga - Panglipurjati, Puspaningtyas (Jurnal Atma Inovasia, 2021)
Shallots are one of the village potentials in Banguncipto Village. Shallots themselves can be utilized in an assortment of things, from fried onions to chili sauce. The process is quite easy, starting with cutting the shallots and then coating them with flour and then frying them in hot oil and then packing them. By producing shallots, the price of the product will increase compared to selling shallots directly and at the same time expanding employment. Kartu Keluarga itself is a family identity card containing informations on the name, structure and connections in the family, just as the identity of family members. Number of people, particularly youthful family, don't have a clue how to deal with a family card, especially in today's online era, there are many things that must be prepared. To make a family card, the maker must make a cover letter first then fill out the formular for making a family card. If everything has been signed, the files will be forwarded and processed then the maker takes the family card that has been made.